An action research addressing errors in the data analysis process in a content operations team in Company XYZ - Lipat, Jan Paolo M. (Animo Repository, 2021)
This action research is about addressing errors in the data analysis process in our Content Operations team within Company XYZ. As a global financial information company, quality is one of the cornerstones of the organization’s value proposition, mission and strategies. In the process of identifying the said issue, the researcher and the collaborators for this study have summarized the observed manifestations of the issue and in highlighting its significance, have formulated justifications and mapped the effects of the error to the other metrics of the organization. With continuous collaboration and inquiry with the rest of the team, a force field diagram has been created to map the causes of the said issue. The primary objective of the study is to improve how the team addresses the errors that it encounters - to improve data quality, lower data integrity queries from the client and minimize the negative effects of errors. With the help of various related literatures and studies, the team decided to adapt the error management concept by Van Dyck et al. as an additional strategy into dealing with errors. The concept primarily exhorts organizations to plan on what can be done after an error has occurred and promote the positive effects of its occurrence rather than the negative. The 2 action research cycles were framed with respect to the common practices indicated in the error management theory. The first cycle was aimed at improving communication about errors and sharing error knowledge and the second cycle was directed towards enabling quick error detection and damage control. The process of change has been guided by Lewin’s Change Management Framework. The said interventions yielded into positive results/feedback which includes decreased error count and quicker error detection and correction. Through this study, interdependencies between the common error management practices were realized, including the need for the acceptance of the reality of errors.